A perovskite catalyst and its preparation method and application

By regulating the proportion and structure of perovskite surface elements, a three-dimensional ordered macroporous perovskite catalyst modified with nanosilicon dioxide was prepared, which solved the problem of reduced activity and stability of perovskite catalysts during high-temperature roasting. Excellent performance in high concentration hydrogen peroxide, methanol decomposition and low carbon alkane conversion reactions were achieved.

CN116265092BActive Publication Date: 2025-01-17DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111539128.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-16
Publication Date
2025-01-17
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

The surface area of ​​perovskite catalysts decreases and severe sintering during high-temperature calcination, resulting in a decrease in activity. There are stability problems in reactions such as catalytic decomposition of hydrogen peroxide and methanol decomposition, especially the thermal stability of copper catalysts is poor. Easy to heat sinter.

Method used

Through chemical etching and high-temperature atmosphere calcination, the A/B position element ratio of perovskite surface is regulated, and a three-dimensional ordered macroporous perovskite catalyst modified by nanosilica is prepared, using emulsion polymerization and multi-step roasting process. Form a catalyst with high activity and stability.

Benefits of technology

The activity and stability of the catalyst are significantly improved, the performance of hydrogen peroxide decomposition and methanol decomposition reaction is enhanced, the service life of the catalyst is extended, and sintering is inhibited in the low-carbon alkane conversion reaction, and the mechanical strength is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003413792560000181
    Figure BDA0003413792560000181
  • Figure BDA0003413792560000221
    Figure BDA0003413792560000221
  • Figure BDA0003413792560000231
    Figure BDA0003413792560000231
Patent Text Reader

Abstract

The present application discloses a perovskite catalyst and its preparation method and application. The perovskite catalyst is modified by silicon dioxide to form a three-dimensional ordered macroporous perovskite catalyst; wherein the perovskite is AFe x M 1‑x O3, A is selected from at least two of La, Ce, Ca, Sr and Ba, M is selected from at least one of Cr, Mn, Co or Cu, and 0≤x≤1. The present invention regulates the A / B element ratio on the surface of the three-dimensional macroporous perovskite modified with silica by chemical etching and high-temperature atmosphere calcination. The method can significantly increase the proportion of perovskite and the number of active sites in the catalyst, while effectively inhibiting the sintering of the catalyst, so that the catalyst has both high activity and high stability. The catalyst is simple to prepare and has good repeatability. It exhibits excellent reaction performance in the decomposition of high-concentration hydrogen peroxide, the decomposition of methanol and the conversion of chemical chain low-carbon alkanes, and has potential application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a perovskite-type catalyst and a preparation method and application thereof, belonging to the field of catalyst preparation. Background Art

[0002] Perovskite oxides are widely used in chemical chain alkane conversion due to their stable structure, diverse composition, easy characterization of compound structure, and adjustable valence, ratio and vacancy content of elements over a wide range. Literature research shows that the catalytic performance of perovskite materials depends not only on the particle size, crystal plane, morphology and carrier, but also on the performance of the material by adjusting the surface structure. Due to the complexity of its components, the distribution of surface elements of perovskite materials is often very different from that of the bulk phase, resulting in a wide range of catalytic performance. Yildiz et al. (J.Am.Chem.Soc.2013,135,7909-7925) studied La 0.8 D 0.2 The cation segregation phenomenon of MnO3 (D = Ca, Sr, Ba) was found to drive the segregation of dopants on the perovskite surface by affecting the elastic potential energy and electrostatic interaction, respectively, directly affecting the reaction performance and stability of the cathode in ORR. Irvine et al. (Nat. Mater. 2016, 15, 1010-1016) found that the cation size mismatch, oxygen vacancies and cation vacancy distribution drive the segregation of dopants on the perovskite surface by affecting the elastic potential energy and electrostatic interaction, respectively. 0.8 Sr 0.2 The surface of CoO3 is modified with B-site ions of different reducibility, resulting in differences in the oxygen exchange rate in ORR. In terms of thermochemistry, Wu et al. (Angew. Chem. 2017, 129, 9952-9956) controlled the termination sites on the surface of perovskite to regulate the reaction selectivity, used different treatment methods to enrich Sr or Ti on the surface of SrTiO3, and changed the selectivity of 2-propanol dehydrogenation products by adjusting the acidity and alkalinity of the catalyst. From the above studies, it can be seen that regulating the distribution of surface elements will significantly affect the reaction activity of perovskite catalysts.

[0003] However, since the perovskite material needs to be calcined at high temperature (generally >800°C) during the synthesis process, the surface area of ​​the catalyst decreases rapidly, sintering is severe, and the particle distribution is uneven, which reduces its activity. Various methods can be adopted to improve the sintering resistance of the catalyst, such as (1) loading it on a suitable carrier. Kuhn et al. (ACS Catal. 2018, 8, 4, 3021-3029) found that silica-supported perovskite oxides can enhance the ability of CO2 to convert into CO at low temperatures. Although the sintering problem of the catalyst is alleviated to a certain extent by constructing a supported oxygen carrier, its loading amount is often low; and when the perovskite loading amount is increased, the carrier is coated with perovskite, and the gain and loss of a large amount of lattice oxygen during the reaction process easily leads to the sintering and growth of the oxygen carrier particles, making it impossible to balance the oxygen loading and cyclic stability. (2) The perovskite catalyst with a core-shell structure is prepared by the template method, which can increase the loading amount and increase the specific surface area, but the shell material will cover the surface active sites, resulting in performance degradation. (3) Nanoscale perovskite catalysts were obtained at a relatively low temperature by mechanical ball milling, which effectively increased the specific surface area of ​​the catalyst. However, there were problems with the initial high activity and rapid sintering during the reaction.

[0004] In the field of aerospace propulsion, perovskite as a catalyst has unique performance advantages in the catalytic decomposition technology of high-concentration hydrogen peroxide at the propulsion stage. Catalytic decomposition is a major application mode of hydrogen peroxide propellant, that is, it is decomposed into high-temperature oxygen-rich combustion gas composed of O2 and H2O under the action of a catalyst. It can be used as both a working fluid for monocomponent power and an oxidant for bicomponent power. Among them, the catalyst is one of the core technologies that determine the application efficiency of the hydrogen peroxide power system. Conventional hydrogen peroxide catalytic decomposition technology usually uses metal Ag as an active component, which has high reaction activity. However, during the catalytic decomposition of hydrogen peroxide, it is affected by the ionization of elemental Ag, resulting in a serious loss of the Ag active component, which greatly reduces the working time of the catalyst. The catalyst bed flow resistance (pre-spray pressure-chamber pressure) increases significantly within hundreds of seconds, which in turn restricts the stable working cycle of the power system.

[0005] The application of perovskite catalysts in methanol decomposition reactions is also an important research direction. Methanol is widely available, easy to store and transport, has a high energy conversion efficiency, and the reaction products are mainly water and a small amount of carbon dioxide. It is a green energy source. Methanol is a high-energy fuel with great potential in the future and a good carrier of H2 and CO. Although certain breakthroughs have been made in the research of methanol low-temperature cracking catalyst systems, there are still some problems to be solved. For example, Cu-based catalysts have excellent catalytic properties such as good catalytic activity and selectivity at low temperatures, which makes them more suitable for methanol decomposition reactions. However, copper-based catalysts have poor thermal stability and are prone to thermal sintering.

[0006] The application of perovskite catalysts in the conversion of low-carbon alkanes (methane, ethane and propane) is also a hot topic of research. Natural gas is an important part of my country's energy composition, and it is of great significance to convert low-carbon alkanes (methane, ethane and propane) into high-value-added chemicals. Chemical chain reforming technology uses the lattice oxygen of oxygen carriers as the oxygen source to selectively oxidize alkanes, and then regenerates the reduced oxygen carriers using O2, CO2 or H2O, thereby realizing the recycling of catalysts, effectively avoiding direct contact between alkanes and gaseous oxygen, inhibiting excessive oxidation of alkanes, inhibiting the accumulation of large amounts of carbon deposits on active centers, and increasing the service life of the catalyst. Summary of the invention

[0007] The present invention provides a method for preparing a nano-silica modified three-dimensional ordered macroporous perovskite catalyst, the purpose of which is to adjust the A / B element ratio on the surface of the perovskite by chemical etching and high-temperature (900-1200°C) atmosphere calcination, so as to achieve excellent activity and stability in high-concentration hydrogen peroxide decomposition, methanol decomposition and chemical chain low-carbon alkane conversion reactions.

[0008] In one aspect of the present application, a perovskite catalyst is provided, wherein the perovskite catalyst is modified by nano-silicon dioxide to form a perovskite catalyst;

[0009] Among them, perovskite is AFe x M 1-x O3, A is selected from at least two of La, Ce, Ca, Sr and Ba, M is selected from at least one of Cr, Mn, Co or Cu, and 0≤x≤1.

[0010] The perovskite-type catalyst has three-dimensional ordered macropores.

[0011] Another aspect of the present application provides a method for preparing the above-mentioned perovskite-type catalyst, the preparation method comprising:

[0012] (1) preparing polymethyl methacrylate microspheres by emulsion polymerization;

[0013] (2) mixing a precursor containing metal element A, a precursor containing Fe, a precursor containing metal element M, nano-silicon dioxide and water, and adding ethylene glycol and citric acid to form a mixed solution;

[0014] (3) adding the mixed solution obtained in step (2) to polymethyl methacrylate microspheres, and performing impregnation, drying, calcination I, and calcination II;

[0015] (4) Calcination III to obtain the perovskite catalyst.

[0016] As a specific embodiment, the preparation method comprises:

[0017] (1) preparing polymethyl methacrylate microspheres (PMMA); (2) adding some precursors of La, Ce, Ca, Sr, Ba, Fe, Cr, Mn, Co and Cu and nano-silicon dioxide (10-20 nm) to deionized water in a stoichiometric ratio under stirring, wherein the mass ratio of metal to silicon dioxide is (2-20):1; (3) adding ethylene glycol and citric acid, wherein the molar ratio of citric acid to metal ions is (1-3):1; (4) adding the above liquids to the prepared PMMA, immersing for 12 hours, filtering, and drying at 80°C overnight; (5) calcining the ground powder at 500°C (argon) for 4-10 hours; (6) subsequently calcining at 800°C (air) for 4-10 hours.

[0018] The A / B element ratio on the surface of the three-dimensional ordered macroporous perovskite catalyst is adjusted by etching with dilute nitric acid, dilute hydrochloric acid, acetic acid, ethanol or ethylene glycol and calcining at 900-1200° C. and different oxygen partial pressures (argon, air, oxygen) for 4-10 hours.

[0019] Optionally, the La precursor is selected from at least one of La(NO3)3·6H2O and LaCl3;

[0020] Optionally, the Ce precursor is selected from at least one of Ce(NO3)3·6H2O and CeCl3·7H2O;

[0021] Optionally, the precursor of Ca is selected from at least one of Ca(NO3)2 and CaCl2;

[0022] Optionally, the Sr precursor is selected from at least one of Sr(NO3)2 and SrCl2·6H2O;

[0023] Optionally, the precursor of Ba is selected from at least one of Ba(NO3)2 and BaCl2;

[0024] Optionally, the Fe precursor is selected from at least one of Fe(NO3)3·9H2O and FeCl3;

[0025] Optionally, the Cr precursor is selected from at least one of Cr(NO3)3·9H2O and CrCl3.6(H2O);

[0026] Optionally, the precursor of Mn is selected from at least one of Mn(NO3)2·6H2O and MnCl2;

[0027] Optionally, the Co precursor is selected from at least one of Co(NO3)2·6H2O and CoCl2·6(H2O);

[0028] Optionally, the Cu precursor is selected from at least one of Cu(NO3)2·3H2O and CuCl2.

[0029] Optionally, the silicon dioxide is selected from at least one of nano silicon dioxide, nano silicon dioxide sol, and hydrophilic fumed silicon dioxide;

[0030] Optionally, the particle size of the nano-silicon dioxide is 10 to 20 nm;

[0031] Optionally, the mass ratio of the total mass of the metal elements A and B to the mass of silicon dioxide is (2-20):1;

[0032] Optionally, the molar ratio of citric acid to total metal ions is (1-3):1.

[0033] Optionally, the calcination I is carried out in an argon atmosphere at a temperature of 500 to 600° C. for 4 to 10 hours;

[0034] The calcination II is carried out in an air atmosphere at a temperature of 700 to 800° C. for 4 to 10 hours;

[0035] The calcination III is carried out in one of argon, air and oxygen atmospheres, the calcination III temperature is 900-1200° C., and the calcination III time is 4-10 hours.

[0036] The A / B element ratio on the perovskite surface was adjusted by calcining at 900-1200°C and different oxygen partial pressures (argon, air, oxygen) for 4-10 hours.

[0037] Optionally, the etchant is selected from at least one of dilute nitric acid, dilute hydrochloric acid, acetic acid, ethanol or ethylene glycol. By etching with dilute nitric acid, dilute hydrochloric acid, acetic acid, ethanol or ethylene glycol, the exposure degree of the perovskite surface is effectively increased and the proportion of surface B-site elements is increased.

[0038] In another aspect of the present application, there is provided a use of the above-mentioned perovskite catalyst or the perovskite catalyst obtained according to the above-mentioned preparation method in the decomposition of high-concentration hydrogen peroxide, wherein the mass concentration of the hydrogen peroxide is 70% to 98%.

[0039] The reaction temperature is 0~80℃.

[0040] It can be used in the field of green aerospace propulsion.

[0041] Optionally, the application may be used in aerospace propulsion systems;

[0042] Optionally, the aerospace propulsion system includes at least one of an auxiliary power system and a main propulsion system of aerospace propulsion.

[0043] Optionally, the catalyst and hydrogen peroxide are loaded in an in-situ oxygen source generator of a liquid monopropellant thrust chamber, a gas generator reaction chamber, a liquid-liquid bipropellant engine or a solid-liquid hybrid engine of a power system;

[0044] It can operate in pulse mode to control the continuous opening and closing of the valve and in steady-state mode to control the continuous opening of the valve. 90 <600ms fast response, >30g / cm 2 · High bed load and long-term steady-state working capability of >1000s.

[0045] Another aspect of the present application provides an application of the above-mentioned perovskite catalyst or the perovskite catalyst obtained according to the above-mentioned preparation method in a methanol decomposition reaction, wherein the mass fraction of water in the methanol is 0 to 50%, the reaction temperature is 200 to 350°C, the pressure is 1 to 20 bar, and the stable working life of the perovskite catalyst is greater than 200h.

[0046] In another aspect of the present application, there is provided a use of the above-mentioned perovskite catalyst or the perovskite catalyst obtained according to the above-mentioned preparation method in a chemical chain low-carbon alkane conversion reaction, wherein the low-carbon alkane is selected from at least one of methane, ethane, and propane;

[0047] The reaction is carried out in a fixed bed reaction;

[0048] Preferably, when the low carbon alkane is methane, the methane is oxidized to synthesis gas at a reaction temperature of 700 to 900°C;

[0049] Preferably, when the low carbon alkane is ethane, the ethane is oxidized to ethylene at a reaction temperature of 600 to 750°C;

[0050] Preferably, when the low carbon alkane is propane, the propane is oxidized to propylene at a reaction temperature of 500-700°C.

[0051] In the application of the catalyst in the conversion of chemical chain low-carbon alkanes, the volume fraction of methane, ethane or propane is 5% to 100%, and the flow rate is 30 to 100 mL / min; the volume fraction of O2, CO2 or H2O is 5% to 100%, and the flow rate is 30 to 100 mL / min.

[0052] The beneficial effects of this application include:

[0053] 1. Compared with traditional supported and core-shell structured perovskite catalysts, the nano-silica modified three-dimensional ordered macroporous perovskite catalyst involved in the present invention can significantly increase the proportion of perovskite and the number of active sites in the catalyst, while effectively inhibiting the sintering of the catalyst, thereby making the catalyst have both high activity and high stability.

[0054] 2. In the application of high-concentration hydrogen peroxide decomposition, compared with Ag-based catalysts, the nano-silica-modified three-dimensional ordered macroporous perovskite catalyst of the present invention has not only higher hydrogen peroxide catalytic decomposition activity, but also has significant performance advantages in terms of reaction stability. 2 ·s, the flow resistance of the catalyst bed hardly fluctuates within the thousand-second range, which plays a key technical role in significantly improving the service life of aerospace vehicles.

[0055] 3. In the application of methanol decomposition, compared with the traditional Cu-based catalyst, the nano-silica modified three-dimensional ordered macroporous perovskite catalyst designed in the present invention can not only improve the activity of methanol low-temperature decomposition, but also improve the stability of the reaction, so that the catalyst maintains high activity at >200h.

[0056] 4. In the application of chemical chain low-carbon alkane conversion, the three-dimensional ordered macroporous perovskite catalyst modified by nano-silica designed in the present invention regulates the A / B site ratio through chemical etching and high-temperature atmosphere calcination, significantly increases the proportion of perovskite and the number of active sites in the catalyst, and has a low catalyst loss rate and high mechanical strength, while effectively inhibiting catalyst sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The XRD diffraction spectra of the catalysts prepared in Comparative Examples 1 and 3 of the present invention are shown.

[0058] Figure 2 This is the SEM spectrum of the catalyst prepared in Example 1 of the present invention.

[0059] Figure 3 This is the HRTEM spectrum of the catalyst prepared in Example 1 of the present invention.

[0060] Figure 4 LEIS spectra of the catalysts prepared in Comparative Examples 3 and 4 of the present invention.

[0061] Figure 5 This is a high concentration hydrogen peroxide decomposition performance diagram of the catalyst prepared in Example 3 of the present invention.

[0062] Figure 6 Schematic diagram of a liquid monopropellant thrust chamber, a gas generator reaction chamber, a liquid-liquid bipropellant engine, and an in-situ oxygen source generator for a solid-liquid hybrid engine equipped with a catalyst prepared by the present invention.

[0063] Figure 7 This is a temperature change diagram of the catalyst prepared in Example 3 of the present invention during a high concentration hydrogen peroxide process. DETAILED DESCRIPTION

[0064] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0065] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0066] The present invention controls the surface structure of the three-dimensional ordered macroporous perovskite catalyst modified by nano-silica by controlling the catalyst calcination temperature and oxygen partial pressure to achieve application in high-concentration hydrogen peroxide decomposition, methanol decomposition and chemical chain low-carbon alkane conversion reactions. x M 1-x O3, A is two or more elements among La, Ce, Ca, Sr and Ba, M is Cr, Mn, Co or Cu, 0≤x≤1.

[0067] The specific preparation method is as follows: (1) preparing polymethyl methacrylate microspheres (PMMA); (2) adding some precursors of La, Ce, Ca, Sr, Ba, Fe, Cr, Mn, Co and Cu and nano-silicon dioxide (10-20 nm) to deionized water in a stoichiometric ratio under stirring, wherein the mass ratio of metal to silicon dioxide is (2-20):1; (3) adding ethylene glycol and citric acid, wherein the molar ratio of citric acid to metal ions is (1-3):1; (4) adding the above liquid to the prepared PMMA, immersing for 12 hours, filtering, and drying at 80°C overnight; (5) roasting the ground powder at 500-600°C (argon) for 4-10 hours; (6) then roasting at 800-900°C (air) for 4-10 hours.

[0068] The silicon dioxide added to the catalyst during the synthesis process can be selected from nano silicon dioxide, nano silicon dioxide sol, and hydrophilic fumed silicon dioxide.

[0069] The catalyst uses dilute nitric acid, dilute hydrochloric acid, acetic acid, ethanol or ethylene glycol to etch the perovskite surface during post-treatment.

[0070] The catalyst is calcined at temperatures of 900°C, 1000°C, 1100°C and 1200°C during post-treatment.

[0071] The catalyst is used in the decomposition of high-concentration hydrogen peroxide, and the mass concentration of hydrogen peroxide is 70%, 90% and 98%.

[0072] The catalyst is used in the decomposition of high-concentration hydrogen peroxide at ambient temperatures of 0°C, 20°C, 50°C and 80°C.

[0073] The application of the catalyst in the decomposition of high-concentration hydrogen peroxide can be used in the auxiliary power system and the main propulsion system of aerospace propulsion.

[0074] The catalyst is used in the decomposition of high-concentration hydrogen peroxide and can be assembled in a liquid monopropellant thrust chamber, a gas generator reaction chamber, a liquid-liquid bipropellant engine or an in-situ oxygen source generator of a solid-liquid hybrid engine of a power system.

[0075] The application of the catalyst in the decomposition of high-concentration hydrogen peroxide can implement pulse mode operation for controlling the continuous opening and closing of the valve and steady-state mode operation for continuous normal opening.

[0076] The catalyst is used in methanol decomposition, the mass fraction of water in methanol is 0%-50%, the reaction temperature is 200-350°C, and the pressure is 1-20 bar.

[0077] The catalyst is used in chemical chain low-carbon alkane conversion. The reaction temperature of partial oxidation of methane in a fixed bed reactor is 700-900°C; the temperature of oxidative dehydrogenation of ethane is 600-750°C; the temperature of oxidative dehydrogenation of propane is 500-700°C.

[0078] The catalyst is used in the conversion of chemical chain low-carbon alkanes, with a volume fraction of methane, ethane or propane of 5 to 100% and a flow rate of 30 to 100 mL / min; a volume fraction of O2, CO2 or H2O of 5 to 100% and a flow rate of 30 to 100 mL / min, and a quadruple mass spectrometer is used to analyze the reactor outlet composition online.

[0079] Example 1

[0080] Nano-silica and La, Sr, Fe, and Cr precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1, and the above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 1200°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 0.8 Co 0.2 O3 / SiO2.

[0081] Example 2

[0082] Nano-silica and La, Ce, Fe, and Co precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1, and the above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 1200°C in oxygen for 5 hours to obtain 3DOM La 0.5 Ce 0.5 Fe 0.8 Co 0.2 O3 / SiO2.

[0083] Example 3

[0084] Nano-silica and La, Sr, Fe, and Mn precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1, and the above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 1200°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 0.8 Mn 0.2 O3 / SiO2.

[0085] Example 4

[0086] Nano-silica and La, Sr, Fe, and Co precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1, and the above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 1200°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 0.8 Cr 0.2 O3 / SiO2.

[0087] Example 5

[0088] Under stirring, nano-silica and La, Sr, Fe, and Cu precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1, and the above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 1200°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 0.8 Cu 0.2 O3 / SiO2.

[0089] Example 6

[0090] The same as Example 1, but different from Example 1 is that the silicon dioxide is nano silicon dioxide.

[0091] Example 7

[0092] The same as Example 1, but different from Example 1 is that the silicon dioxide is nano-silica sol.

[0093] Example 8

[0094] The same as Example 1, but different from Example 1 is that the silicon dioxide is hydrophilic fumed silicon dioxide.

[0095] Example 9

[0096] Same as Example 1, except that the mass ratio of metal to silicon dioxide is 5:1.

[0097] Example 10

[0098] Same as Example 1, except that the mass ratio of metal to silicon dioxide is 15:1.

[0099] Embodiment 11

[0100] Same as Example 1, except that the molar ratio of citric acid to metal ions is 2:1.

[0101] Example 12

[0102] Same as Example 1, except that the molar ratio of citric acid to metal ions is 1.5:1.

[0103] Embodiment 13

[0104] Same as Example 1, except that after drying at 80°C overnight, the mixture was calcined at 550°C (argon) for 5h.

[0105] Embodiment 14

[0106] Same as Example 1, except that after drying at 80°C overnight, the mixture was calcined at 600°C (argon) for 5h.

[0107] Embodiment 15

[0108] Same as Example 1, except that after drying at 80°C overnight, the mixture was calcined at 500°C (argon) for 8h.

[0109] Example 16

[0110] Same as Example 1, except that after drying at 80°C overnight, the mixture was calcined at 500°C (argon) for 10 h.

[0111] Embodiment 17

[0112] Same as Example 1, except that the sample was calcined at 500°C (argon) for 5 hours and then calcined at 700°C (air) for 5 hours.

[0113] Embodiment 18

[0114] Same as Example 1, except that the sintered product is sintered at 500°C (argon) for 5 hours and then sintered at 750°C (air) for 5 hours.

[0115] Embodiment 19

[0116] Same as Example 1, except that the sintered product was calcined at 500°C (argon) for 5 hours and then calcined at 800°C (air) for 8 hours.

[0117] Embodiment 20

[0118] Same as Example 1, except that the sample was calcined at 500°C (argon) for 5 hours and then calcined at 800°C (air) for 10 hours.

[0119] Embodiment 21

[0120] The same as Example 1, but different from Example 1, the obtained substance is ground into powder, calcined at 800° C. for 5 h, and then calcined at 900° C. for 5 h.

[0121] Embodiment 22

[0122] The same as Example 1, but different from Example 1, the obtained substance is ground into powder, calcined at 800° C. for 5 h, and then calcined at 1000° C. for 5 h.

[0123] Embodiment 23

[0124] The same as Example 1, except that the obtained material was ground into powder, calcined at 800° C. for 5 h, and then calcined at 1100° C. for 5 h.

[0125] Embodiment 24

[0126] Same as Example 1, but different from Example 1 in that the atmosphere during calcination at 1200° C. is air.

[0127] Embodiment 25

[0128] Same as Example 1, but different from Example 1 in that the atmosphere during calcination at 1200° C. is argon.

[0129] Embodiment 26

[0130] The same as Example 1, but different from Example 1 is that the obtained catalyst is etched with dilute nitric acid at room temperature and then dried at 80° C. overnight.

[0131] Embodiment 27

[0132] The same as Example 1, but different from Example 1 is that the obtained catalyst is etched with acetic acid at room temperature and then dried at 80° C. overnight.

[0133] Embodiment 28

[0134] The same as Example 1, but different from Example 1 in that the obtained catalyst is etched with ethylene glycol at room temperature and then dried at 80° C. overnight.

[0135] Embodiment 29

[0136] The same as Example 2, but different from Example 2, the obtained material is ground into powder, calcined at 800° C. for 5 h, and then calcined at 900° C. for 5 h.

[0137] Embodiment 30

[0138] Same as Example 2, except that the obtained material was ground into powder, calcined at 800° C. for 5 h, and then calcined at 1000° C. for 5 h.

[0139] Embodiment 31

[0140] The same as Example 2, but different from Example 2, the obtained material is ground into powder, calcined at 800° C. for 5 h, and then calcined at 1100° C. for 5 h.

[0141] Comparative Example 1

[0142] The precursors of La, Sr and Fe were added into deionized water in a stoichiometric ratio of 0.5:0.5:1.0, dissolved under heating and stirring to obtain a precursor solution, and then citric acid was added, wherein the molar ratio of citric acid to metal ions was 2.5:1, dissolved under heating and stirring, and ammonia water was added to adjust the pH to 7-8, and stirred in a water bath at 80°C until a sol state; the formed sol was placed in a 160°C oven for overnight drying, and calcined at 500°C (argon) for 5h, 800°C (air) for 5h, and 1200°C in oxygen for 5h to obtain La. 0.5 Sr 0.5 Fe 1.0 O3.

[0143] Comparative Example 2

[0144] Under stirring, nano-silica and La, Sr, and Fe precursors are added to deionized water in a stoichiometric ratio of 0.5:0.5:1.0, wherein the mass ratio of metal to silica is 10:1, and then ethylene glycol and citric acid are added, wherein the molar ratio of citric acid to metal ions is 2.5:1, stirred in a water bath at 80°C, placed in a 160°C oven to dry overnight, calcined at 500°C (argon) for 5h, 800°C (air) for 5h, and 1200°C in oxygen for 5h to obtain La 0.5 Sr 0.5 Fe 1.0 O3 / SiO2.

[0145] Comparative Example 3

[0146] Nano-silica and La, Sr, and Fe precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:1.0 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1. The above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 1200°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 1.0 O3 / SiO2.

[0147] Comparative Example 4

[0148] Nano-silica and La, Sr, and Fe precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:1.0 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1. The above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 900°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 1.0 O3 / SiO2.

[0149] Comparative Example 5

[0150] The precursors of La, Sr, Fe and Cr were added into deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2, dissolved under heating and stirring to obtain a precursor solution, and then citric acid was added, wherein the molar ratio of citric acid to metal ions was 2.5:1, dissolved under heating and stirring, and ammonia water was added to adjust the pH to 7-8, and stirred in a water bath at 80°C until a sol state; the formed sol was placed in a 160°C oven for overnight drying, and calcined at 500°C (argon) for 5h, 800°C (air) for 5h, and 1200°C in oxygen for 5h to obtain La. 0.5 Sr 0.5 Fe 0.8 Cr 0.2 O3.

[0151] Comparative Example 6

[0152] Nano-silica and La, Sr, Fe, and Cr precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1, and the above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 1200°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 0.8 Cr 0.2 O3 / SiO2.

[0153] Comparative Example 7

[0154] The precursors of La, Sr, Fe and Cr were added into deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2, dissolved under heating and stirring to obtain a precursor solution, and then citric acid was added, wherein the molar ratio of citric acid to metal ions was 2.5:1, dissolved under heating and stirring, and ammonia water was added to adjust the pH to 7-8, and stirred in a water bath at 80°C until a sol state; the formed sol was placed in a 160°C oven for overnight drying, and calcined at 500°C (argon) for 5h, 800°C (air) for 5h, and 900°C in oxygen for 5h to obtain La. 0.5 Sr 0.5 Fe 0.8 Cr 0.2 O3.

[0155] Comparative Example 8

[0156] Nano-silica and La, Sr, Fe, and Cr precursors were added to deionized water in a stoichiometric ratio of 0.5:0.5:0.8:0.2 under stirring, wherein the mass ratio of metal to silica was 10:1, and then ethylene glycol and citric acid were added, wherein the molar ratio of citric acid to metal ions was 2.5:1, and the above liquids were added to methyl methacrylate microspheres prepared by emulsion polymerization, and the mixture was filtered after immersion for 12 hours, dried at 80°C overnight, and then the ground powder was calcined at 500°C (argon) for 5 hours, then calcined at 800°C (air) for 5 hours, and calcined at 900°C in oxygen for 5 hours to obtain 3DOM La 0.5 Sr 0.5 Fe 0.8 Cr 0.2 O3 / SiO2.

[0157] Comparative Example 9

[0158] The same as Comparative Example 5, but different from Comparative Example 5, is that the atmosphere during calcination at 1200° C. is air.

[0159] Comparative Example 10

[0160] The same as Comparative Example 5, but different from Comparative Example 5, is that the atmosphere during calcination at 1200° C. is argon.

[0161] Comparative Example 11

[0162] The same as Comparative Example 6 is different from Comparative Example 6 in that the atmosphere during calcination at 1200° C. is air.

[0163] Comparative Example 12

[0164] The same as Comparative Example 6, but different from Comparative Example 6, is that the atmosphere during calcination at 1200° C. is argon.

[0165] Comparative Example 13

[0166] The same as Comparative Example 7 is different from Comparative Example 7 in that the atmosphere during calcination at 900° C. is air.

[0167] Comparative Example 14

[0168] The same as Comparative Example 7, but different from Comparative Example 7, is that the atmosphere during calcination at 900° C. is argon.

[0169] Comparative Example 15

[0170] The same as Comparative Example 8, but different from Comparative Example 8, is that the atmosphere during calcination at 900° C. is air.

[0171] Comparative Example 16

[0172] The same as Comparative Example 8, but different from Comparative Example 8, is that the atmosphere during calcination at 900° C. is argon.

[0173] Test Case

[0174] The La obtained in Comparative Example 1 0.5 Sr 0.5 Fe 1.0 O3 and 3DOM La obtained in Example 1 0.5 Sr 0.5 Fe 1.0 X-ray diffraction tests of O3 / SiO2 catalysts were carried out on PANalytical X′Pert-Pro-1 with a copper target K α The light source is λ = 0.15432nm, the tube voltage is 40kV, and the tube current is 40mA. The test results show that the catalysts all form a perovskite phase with a good structure. Figure 1 .

[0175] 3DOM La of Example 1 0.5 Sr 0.5 Fe 0.8 Cr 0.2 The scanning electron microscope (SEM) characterization of the O3 / SiO2 catalyst was carried out on a JEOL JSM-7800F with an acceleration voltage of 2.0-10.0 kV to observe the microscopic morphology. The characterization results showed that the catalyst formed a three-dimensional macroporous material. Figure 2 .

[0176] 3DOM La of Example 1 0.5 Sr 0.5 Fe 0.8 Cr 0.2 The O3 / SiO2 catalyst was subjected to high-angle annular dark field scanning transmission electron microscopy (HAADF STEM) to observe the types and arrangement of the outermost atoms. The characterization results showed that the atoms at the A and B positions of the outermost atoms of the catalyst were arranged alternately in a periodic manner in a step-like manner. Figure 3 .

[0177] 3DOM La of Comparative Example 3 0.5 Sr 0.5 Fe 1.0 O3 / SiO2-1200℃ and 3DOMLa of Comparative Example 4 0.5 Sr 0.5 Fe 1.0 The O3 / SiO2-900℃ catalyst was subjected to low energy particle scattering spectrum test (LEIS) to analyze the element composition and content of the surface layer. Characterization results 3DOM La 0.5 Sr 0.5 Fe 1.0 The top layer of O3 / SiO2-1200℃ is mainly composed of Fe, 3DOMLa 0.5 Sr 0.5 Fe 1.0 The topmost layer of O3 / SiO2-900℃ is mainly composed of Sr. Figure 4 .

[0178] Application Example 1

[0179] The catalysts of Comparative Examples 1 to 16 and Examples 1 to 31 were assembled in Figure 6 In the in-situ oxygen source generator of the liquid monopropellant thrust chamber and the gas generator reaction chamber shown, under the control of the power system valve, the hydrogen peroxide reaction medium with a mass concentration of 70% is pushed by the gas or transported by the fuel pump into the reaction chamber, and a rapid decomposition reaction occurs after contacting the catalyst, and the ambient temperature is 0.2°C. The test results are shown in Table 1.

[0180] Application Example 2

[0181] The catalysts of Comparative Examples 1 to 16 and Examples 1 to 31 were assembled in Figure 6 In the in-situ oxygen source generator of the liquid monopropellant thrust chamber and the gas generator reaction chamber shown, under the control of the power system valve, the hydrogen peroxide reaction medium with a mass concentration of 90% is pushed by the gas or transported by the fuel pump into the reaction chamber, and a rapid decomposition reaction occurs after contacting the catalyst, and the ambient temperature is 13°C. The test results are shown in Table 1.

[0182] Application Example 3

[0183] The catalysts of Comparative Examples 1 to 16 and Examples 1 to 31 were assembled in Figure 6 In the in-situ oxygen source generator of the liquid-liquid bi-component engine and solid-liquid hybrid engine shown, under the control of the power system valve, the hydrogen peroxide reaction medium with a mass concentration of 90% is pushed by gas or transported by a fuel pump into the reaction chamber, and a rapid decomposition reaction occurs after contacting the catalyst, and the ambient temperature is 84°C. The test results are shown in Table 1.

[0184] Application Example 4

[0185] The catalysts of Comparative Examples 1 to 16 and Examples 1 to 31 were assembled in Figure 6 In the in-situ oxygen source generator of the liquid monopropellant thrust chamber and the gas generator reaction chamber, under the control of the power system valve, the reaction medium of hydrogen peroxide with a mass concentration of 98% is pushed by gas or transported by a fuel pump into the reaction chamber, and a rapid decomposition reaction occurs after contacting the catalyst, and the ambient temperature is 24° C. The test results of the catalyst of Example 3 under different conditions are shown in Table 1.

[0186] Table 1 Hydrogen peroxide catalytic decomposition performance of perovskite-type catalysts

[0187]

[0188] Application Example 5

[0189] The methanol decomposition performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg, and the particle size was 80 to 120 mesh. The water content in methanol was 5%, the flow rate was 0.3 mL / min, the reaction temperature was 250°C, and the reaction pressure was 5 bar. The test results are shown in Table 2.

[0190] Application Example 6

[0191] The performance of methanol decomposition of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg, and the particle size was 80 to 120 mesh. The water content in methanol was 10%, the flow rate was 0.3 mL / min, the reaction temperature was 250°C, and the reaction pressure was 5 bar. The test results are shown in Table 2.

[0192] Application Example 7

[0193] The methanol decomposition performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg, the particle size was 80 to 120 mesh, the water content in methanol was 10%, the flow rate was 0.3 mL / min, the reaction temperature was 250° C., and the reaction pressure was 10 bar.

[0194] The test results are shown in Table 2.

[0195] Application Example 8

[0196] The methanol decomposition performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg, the particle size was 80 to 120 mesh, the water content in methanol was 50%, the flow rate was 0.3 mL / min, the reaction temperature was 250° C., and the reaction pressure was 10 bar.

[0197] The test results are shown in Table 2.

[0198] Application Example 9

[0199] The methanol decomposition performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg, the particle size was 80 to 120 mesh, the water content in methanol was 50%, the flow rate was 0.3 mL / min, the reaction temperature was 300° C., and the reaction pressure was 10 bar.

[0200] The test results are shown in Table 2.

[0201] Table 2 Methanol catalytic decomposition performance of perovskite-type catalysts

[0202] Application Examples catalyst Reaction conditions Methanol conversion rate / % Gas yield / % Application Example 5 Example 5 250℃,5bar 84.2 81.5 Application Example 7 Example 5 250℃,10bar 89.5 87.9 Application Example 9 Example 5 300℃,10bar 93.3 91.4

[0203] Application Example 10

[0204] A fixed bed reactor was used to evaluate the chemical chain methane to synthesis gas performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg and the particle size was 80 to 120 mesh. When the fuel gas composition was 5% CH4 / He, the flow rate was 30 mL / min, the reaction temperature was 800°C, and the reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 5% CO2 / He and a flow rate of 30 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0205] Application Example 11

[0206] A fixed bed reactor was used to evaluate the chemical chain methane to synthesis gas performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg, and the particle size was 80 to 120 mesh. The fuel gas composition was 5% CH4 / He, the flow rate was 50 mL / min, the reaction temperature was 850°C, and the reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 5% CO2 / He and a flow rate of 50 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0207] Application Example 12

[0208] A fixed bed reactor was used to evaluate the chemical chain methane to synthesis gas performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg, and the particle size was 80 to 120 mesh. The fuel gas composition was 20% CH4 / He, the flow rate was 30 mL / min, the reaction temperature was 900°C, and the reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 20% CO2 / He and a flow rate of 30 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0209] Application Example 13

[0210] A fixed bed reactor was used to evaluate the chemical chain methane to synthesis gas performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg, and the particle size was 80 to 120 mesh. The fuel gas composition was 100% CH4 / He, the flow rate was 100 mL / min, the reaction temperature was 900°C, and the reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 100% CO2 / He and a flow rate of 100 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0211] Application Example 14

[0212] The chemical chain ethane to ethylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg and the particle size was 80 to 120 meshes. When the fuel gas composition was 5% C2H6 / He, the flow rate was 30 mL / min, the reaction temperature was 600°C, the reaction pressure was normal pressure, and after the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 5% CO2 / He and a flow rate of 30 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0213] Application Example 15

[0214] The chemical chain ethane to ethylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg and the particle size was 80 to 120 meshes. When the fuel gas composition was 5% C2H6 / He, the flow rate was 50 mL / min, the reaction temperature was 700°C, the reaction pressure was normal pressure, and after the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 5% CO2 / He and a flow rate of 50 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0215] Application Example 16

[0216] The chemical chain ethane to ethylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg and the particle size was 80 to 120 meshes. When the fuel gas composition was 20% C2H6 / He, the flow rate was 30 mL / min, the reaction temperature was 750°C, the reaction pressure was normal pressure, and after the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 20% CO2 / He and a flow rate of 30 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0217] Application Example 17

[0218] The chemical chain ethane to ethylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31 was evaluated using a fixed bed reactor. The catalyst dosage was 100 mg and the particle size was 80 to 120 meshes. When the fuel gas composition was 100% C2H6 / He, the flow rate was 100 mL / min, the reaction temperature was 750°C, the reaction pressure was normal pressure, and after the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 100% CO2 / He and a flow rate of 100 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes, and the above steps were repeated 10 times to test the catalyst stability.

[0219] Application Example 18

[0220] A fixed bed reactor was used to evaluate the chemical chain propane to propylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg and the particle size was 80 to 120 mesh. When the fuel gas composition was 5% C3H8 / He, the flow rate was 30 mL / min and the reaction temperature was 500°C. The reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 5% CO2 / He and a flow rate of 30 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes. The above steps were repeated 10 times to test the catalyst stability.

[0221] Application Example 19

[0222] A fixed bed reactor was used to evaluate the chemical chain propane to propylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg and the particle size was 80 to 120 mesh. When the fuel gas composition was 5% C3H8 / He, the flow rate was 50 mL / min and the reaction temperature was 600°C. The reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 5% CO2 / He and a flow rate of 50 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes. The above steps were repeated 10 times to test the catalyst stability.

[0223] Application Example 20

[0224] A fixed bed reactor was used to evaluate the chemical chain propane to propylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg and the particle size was 80 to 120 mesh. When the fuel gas composition was 20% C3H8 / He, the flow rate was 30 mL / min and the reaction temperature was 600°C. The reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 30 mL / min, and then switched to an oxidizing atmosphere with a composition of 20% CO2 / He and a flow rate of 30 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes. The above steps were repeated 10 times to test the catalyst stability.

[0225] Application Example 21

[0226] A fixed bed reactor was used to evaluate the chemical chain propane to propylene performance of the catalysts prepared in Comparative Examples 1 to 16 and Examples 1 to 31. The catalyst dosage was 100 mg and the particle size was 80 to 120 mesh. When the fuel gas composition was 100% C3H8 / He, the flow rate was 100 mL / min and the reaction temperature was 700°C. The reaction pressure was normal pressure. After the reduction was completed for 10 minutes, it was switched to He purge for 5 minutes with a flow rate of 100 mL / min, and then switched to an oxidizing atmosphere with a composition of 100% CO2 / He and a flow rate of 100 mL / min. Under the corresponding isothermal conditions, the time was 15 minutes. The above steps were repeated 10 times to test the catalyst stability.

[0227] Table 3

[0228] Reaction temperature / ℃ <![CDATA[C2H6 conversion rate / %]]> <![CDATA[C2H4 selectivity / %]]> Example 4 Application Example 16 750 20.1 75.3

[0229] Table 4

[0230] Reaction temperature / ℃ <![CDATA[C3H8 conversion rate / %]]> <![CDATA[C3H6 Selectivity / %]]> Example 2 Application Example 20 600 25.2 49.3

[0231] Table 5

[0232] Reaction temperature / ℃ <![CDATA[CH4 conversion rate / %]]> CO selectivity / % Embodiment 23 Application Example 11 850 67.3 93.5 Embodiment 22 Application Example 11 850 82.2 95.7 Embodiment 21 Application Example 11 850 83.7 96.2 Example 1 Application Example 11 850 86.1 98.1

[0233] Table 6

[0234]

[0235]

[0236] Table 7

[0237] Reaction temperature / ℃ <![CDATA[CH4 conversion rate / %]]> CO selectivity / % Comparative Example 10 Application Example 11 850℃ 10.4 54.5 Comparative Example 15 Application Example 11 850℃ 17.2 60.6 Comparative Example 16 Application Example 11 850℃ 21.8 83.2 Embodiment 24 Application Example 11 850℃ 44.2 85.3 Comparative Example 8 Application Example 11 850℃ 54.6 79.7 Embodiment 21 Application Example 11 850℃ 67.3 93.5

[0238] Table 8

[0239] Reaction temperature / ℃ <![CDATA[CH4 conversion rate / %]]> CO selectivity / % Comparative Example 12 Application Example 11 850℃ 15.3 57.2 Embodiment 25 Application Example 11 850℃ 22.7 65.3 Comparative Example 11 Application Example 11 850℃ 47.5 83.6 Embodiment 24 Application Example 11 850℃ 60.9 86.5 Comparative Example 15 Application Example 11 850℃ 72.3 92.4 Example 1 Application Example 11 850℃ 86.1 98.1

[0240] Table 9

[0241] Reaction temperature / ℃ <![CDATA[CH4 conversion rate / %]]> CO selectivity / % Embodiment 26 Application Example 11 850℃ 93.1 98.0 Embodiment 27 Application Example 11 850℃ 90.2 97.4 Embodiment 28 Application Example 11 850℃ 87.0 97.3

[0242] Table 10 The catalyst prepared in Example 1 was used for cycle testing according to Application Example 11

[0243] cycle <![CDATA[CH4 conversion rate / %]]> CO selectivity / % 1 86.1 98.1 2 85.8 98.7 3 85.3 98.4 4 86.0 98.4 5 85.5 98.3 6 85.8 97.9 7 85.9 97.8 8 86.0 98.3 9 85.7 98.2 10 85.6 87.9

[0244] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A perovskite catalyst, characterized in that: The perovskite-type catalyst is modified by silicon dioxide to form a perovskite-type catalyst; Among them, perovskite is AFe x M 1-x O3, A is selected from at least two of La, Ce, Ca, Sr and Ba, M is selected from at least one of Cr, Mn, Co and Cu, 0≤x≤1; The perovskite catalyst is prepared by the following method: (1) Preparation of polymethyl methacrylate microspheres by emulsion polymerization; (2) mixing a precursor containing the metal element A, a precursor containing the metal element M, silicon dioxide and water, and adding ethylene glycol and citric acid to form a mixed solution; (3) adding the mixed solution obtained in step (2) to polymethyl methacrylate microspheres, and performing impregnation, drying, calcination I, and calcination II; (4) etching the powder obtained in step (3) with an etchant; (5) obtaining the perovskite catalyst by calcining III; The calcination I is carried out in an argon atmosphere at a temperature of 500-600° C. for 4-10 h; The calcination II is carried out in an air atmosphere at a temperature of 700-800° C. for 4-10 h; The calcination III is carried out in one of argon, air and oxygen atmospheres, the calcination III temperature is 900-1200° C., and the calcination III time is 4-10 h; The silicon dioxide is selected from at least one of nano silicon dioxide, nano silicon dioxide sol, and hydrophilic fumed silicon dioxide; The etchant is selected from at least one of dilute nitric acid, dilute hydrochloric acid, acetic acid, ethanol or ethylene glycol; 2. The perovskite-type catalyst according to claim 1, characterized in that The mass ratio of the total mass of the metal elements A and B to the mass of silicon dioxide is (2-20):1; The molar ratio of citric acid to total metal ions is (1-3):

1.

3. Use of the perovskite catalyst according to claim 1 in the decomposition of hydrogen peroxide, characterized in that: The mass concentration of the hydrogen peroxide is 70% to 98%.

4. The use according to claim 3, characterized in that: The application can be used in aerospace propulsion systems; The aerospace propulsion system includes at least one of an auxiliary power system and a main propulsion system of aerospace propulsion.

5. The use according to claim 3, characterized in that: The catalyst and hydrogen peroxide are loaded in the liquid monopropellant thrust chamber, gas generator reaction chamber, liquid-liquid bipropellant engine or in-situ oxygen source generator of the solid-liquid hybrid engine of the power system; It can operate in pulse mode to control the continuous opening and closing of the valve and in steady-state mode to control the continuous opening of the valve. 90 <600ms fast response, >30g / cm 2 · High bed load and long-term steady-state working capability of >1000s.

6. Use of the perovskite catalyst according to claim 1 in a methanol decomposition reaction, characterized in that: The water content in methanol is 0~50%, and the reaction temperature is 200~350 o C, the pressure is 1-20 bar, and the stable working life of the perovskite-type catalyst is greater than 200 h.

7. Use of the perovskite catalyst according to claim 1 in a chemical chain low carbon alkane conversion reaction, characterized in that: The low carbon alkane is selected from at least one of methane, ethane and propane; The reaction is carried out in a fixed bed reaction; When the low carbon alkane is methane, the methane is oxidized to synthesis gas at a reaction temperature of 700-900 o C. The volume fraction of methane in the reduction step is 5% to 100%, and the flow rate is 30 to 100 mL / min. The volume fraction of O2, CO2 or H2O in the oxidation step is 5% to 100%, and the flow rate is 30 to 100 mL / min. When the low carbon alkane is ethane, the ethane is oxidized to ethylene at a reaction temperature of 600-750 o C, the volume fraction of ethane in the reduction step is 5% to 100%, and the flow rate is 30 to 100 mL / min, and the volume fraction of O2, CO2 or H2O in the oxidation step is 5% to 100%, and the flow rate is 30 to 100 mL / min; When the low carbon alkane is propane, the propane is oxidized to propylene at a reaction temperature of 500 to 700 o C, the volume fraction of propane in the reduction step is 5%~100%, and the flow rate is 30~100 mL / min, and the volume fraction of O2, CO2 or H2O in the oxidation step is 5%~100%, and the flow rate is 30~100 mL / min.

Citation Information

Patent Citations

  • Methane selective oxidation catalyst, as well as preparation method and application thereof

    CN104549339A

  • Supported rare-earth perovskite catalyst for purifying diesel vehicle exhaust and preparation method thereof

    CN106423176A